Ethnobotany of Coconut Pulp (Cocos nucifera) and Tofu Pulp (Glycine max) as Main Ingredients for Tempe Menjes Production in Ketapang Village, Mojolangu Sub-District, Malang - Minarno, Eko Budi; Selviana, Selviana; Bahriyah, Wildatul; Sanene, Rachel Avril Yanti Windra (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
Coconut pulp, a by-product of coconut processing for coconut milk or oil, as well as tofu pulp derived from the tofu production process, are crucial local resources within the daily life and cultural context of local communities. This study aims to document traditional knowledge surrounding the utilization of these two pulps, encompassing processing techniques into food products, nutritional values, and their roles in social and cultural activities. Through an ethnobotanical approach, this research explores the potential of these pulps as sources of innovation for more sustainable food development, as well as for preserving the sustainable use of local natural resources. The utilization of coconut and tofu pulp reflects not only local adaptations to the environment but also contributes significantly to maintaining cultural identity and local wisdom. The importance of this research lies in the preservation of ethnobotanical knowledge as part of cultural heritage and as a valuable resource for the sustainability of local communities in Ketapang Village and its surrounding areas.